2018
DOI: 10.1099/ijsem.0.002605
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobacterium solani sp. nov., isolated from potato stems

Abstract: A Gram-stain-negative, non-motile, non-spore-forming bacterium, designated MLS-26-JM13-11, was isolated from potato stems, collected in Guyuan County, Hebei Province, China. Strain MLS-26-JM13-11 could grow at 10-39 °C (optimum, 30 °C), pH 6.0-9.0 (optimum, pH 7.2) and in the presence of 0-4.0 % (w/v) NaCl (optimum, 1.0 % w/v). Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain MLS-26-JM13-11 formed a stable clade with Sphingobacterium bambusae IBFC2009 and Sphingobacterium griseofla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…S3). The results of the polar lipid and isoprenoid quinone analysis obtained from the present study were consistent with the patterns observed in members of the genus Sphingobacterium [3–10].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 91%
See 2 more Smart Citations
“…S3). The results of the polar lipid and isoprenoid quinone analysis obtained from the present study were consistent with the patterns observed in members of the genus Sphingobacterium [3–10].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 91%
“…Briefly, the major protein groups included translation, ribosomal structure and biogenesis (J), transcription (K), signal transduction mechanisms (T), cell wall/membrane/envelope biogenesis (M), carbohydrate transport and metabolism (G), and inorganic ion transport and metabolism (P). While strain M6-31 T and six phylogenetic neighbours possessed cell motility-related genes (N), no genes were observed to be involved in flagella, aligning with the morphology of the genus Sphingobacterium, characterized by the absence of a flagellum [3–10]. A dbCAN2 search revealed candidate genes for carbohydrate-active enzyme families, including glycoside hydrolases (GH), glycosyltransferases (GT), carbohydrate-binding module (CBM), carbohydrate esterases (CE), polysaccharide lyases (PL) and auxiliary activities (AA) across all seven genomes, while the subfamily GH30_4, GH30_5, GH30_6, GH35 and GT2_glyco_transf_2_5 existing only in strain M6-31 T (Table S3).…”
Section: Functional Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria of this genus are characterized by a high concentration of sphingophospholipids and are Gram-stain-negative, non-motile, non-spore-forming, positive for catalase and oxidase, but negative for gelatinase, heparinase and indole production, and have iso-C 15 : 0 , iso-C 15 : 0 2-OH, C 16 : 1 ω7c and C 17 : 0 3-OH as the main fatty acids [3]. Members of the genus Sphingobacterium are widely distributed in various natural environments such as soil, desert, compost, sludge, plant, animal and clinical samples [4][5][6][7][8][9]. Some Sphingobacterium strains are capable of degrading pollutants such as polycyclic aromatic hydrocarbons, pesticides, herbicides and antibiotics [7,[10][11][12].…”
mentioning
confidence: 99%
“…DNA G+C content ranges from 37.3 to 44.5 mol% [4]. These species have been isolated from various environments including raw milk, plants, diverse soil habitats, faeces, activated sludge, clinical specimens, freshwater habitats and nodule surface of soybean and include Sphingobacterium terrae [4], Sphingobacterium bovisgrunnientis [5], Sphingobacterium tabacisoli [6], Sphingobacterium solani [7], Sphingobacterium composti [8], Sphingobacterium cellulitidis [9], Sphingobacterium yanglingense [10], Sphingobacterium suaedae [11], Sphingobacterium caeni [12] and Sphingobacterium corticibacter [13]. Recently, Sphingobacterium olei [14], Sphingobacterium chungjuense [15] and Sphingobacterium cavernae [16] were reported.…”
Section: Full-textmentioning
confidence: 99%